2018
DOI: 10.1134/s0012496618030031
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium Oxide Enhances Escherichia coli SOS Response Induced by Genotoxicants

Abstract: It has been demonstrated that deuterium oxide enhances the SOS response of Escherichia coli cells induced by chemical genotoxicants and mutagens. This demonstrates that the heavy nonradioactive hydrogen isotope deuterium can be considered to be a comutagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…In this regard, the importance of water for the implementation of physiological processes is extremely high, but it might vary and differ for each of its nine isotopologues: 1 H 2 16 O, 1 HD 16 O, D 2 16 O, 1 H 2 17 O, 1 HD 17 O, D 2 17 O, 1 H 2 18 O, 1 HD 18 O, D 2 18 O. Some of them, which predominantly contain lighter isotopes, can have in certain concentrations a stimulating effect on functional activity of living systems [5], other isotopologues, including mainly heavy isotopes, are able to inhibit vital processes, especially at high concentrations of deuterium [6,7], and in some cases it was observed that variation of deuterium concentration (both increasing and decreasing its content in water) can enhance the functional activity of living systems [8]. In this regard it is very important to know about the peculiar features of use of certain isotopologues of water for regulation of metabolic processes in a body, and for monitoring of the anabolism and catabolism state of biological substances in various diseases [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the importance of water for the implementation of physiological processes is extremely high, but it might vary and differ for each of its nine isotopologues: 1 H 2 16 O, 1 HD 16 O, D 2 16 O, 1 H 2 17 O, 1 HD 17 O, D 2 17 O, 1 H 2 18 O, 1 HD 18 O, D 2 18 O. Some of them, which predominantly contain lighter isotopes, can have in certain concentrations a stimulating effect on functional activity of living systems [5], other isotopologues, including mainly heavy isotopes, are able to inhibit vital processes, especially at high concentrations of deuterium [6,7], and in some cases it was observed that variation of deuterium concentration (both increasing and decreasing its content in water) can enhance the functional activity of living systems [8]. In this regard it is very important to know about the peculiar features of use of certain isotopologues of water for regulation of metabolic processes in a body, and for monitoring of the anabolism and catabolism state of biological substances in various diseases [9].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a disbalance arises between the rate of damage accumulation and the rate of repair of the initial DNA structure by the repair enzymes, leading to the accumulation of damage in the DNA structure. As a result, the SOS response in a cell is activated, providing the repair of the damaged DNA regions [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…№9 дающего действия на ДНК: диоксидин (10 -5 моль/л), индуцирующий образование свободных форм кислорода; фурацилин (2,5•10 -3 моль/л), образующий аддукт с ДНК и подавляющий размножение микроорганизмов; налидиксовая кислота (10 -3 моль/л), подавляющая репликацию ДНК путем ингибирования ДНК-гиразы. Процедура проведения экспериментов описаны в работах [1,3,4]. Эксперимент проводился в двух вариантах.…”
Section: материалы и методыunclassified
“…Во всех случаях статистическая значимость эффектов дейтерирования оказалась исключительно высокой (р < 0,001). Ранее потенцирующий эффект оксида дейтерия также был продемонстрирован в работах со стандартными мутагенами, наиболее часто используемыми в генотоксикологии: 4-нитрохолин-1-оксидом, [3] метилметансульфонатом, N-нитрозо-N-метилмочевиной [4].…”
Section: основные результатыunclassified